2009
DOI: 10.1111/j.1600-0838.2008.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute sport‐related stressors, coping, and emotion among professional rugby union players during training and matches

Abstract: The purpose of this study was to examine acute sport‐related stressors, coping, and emotion among a sample of professional rugby union players during training and matches. Five professional rugby union players maintained diaries for 31 days. The diaries consisted of a stressor checklist and an open‐ended stressor response section, an open‐ended coping response section, a Likert‐type evaluation of coping effectiveness, a best‐of‐fit emotional response section, and a Likert‐type evaluation of emotional intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 32 publications
6
64
1
4
Order By: Relevance
“…The average intensity for the positive and negative emotions was of similar magnitude reported by the Rugby Union athletes in the Nicholls, Jones et al, 2009. study.…”
Section: Emotion Intensitysupporting
confidence: 61%
See 3 more Smart Citations
“…The average intensity for the positive and negative emotions was of similar magnitude reported by the Rugby Union athletes in the Nicholls, Jones et al, 2009. study.…”
Section: Emotion Intensitysupporting
confidence: 61%
“…Nicholls, Jones et al (2009) found that Caucasian and Fijian Rugby Union athletes experienced more negative emotions, whereas the Malaysian tenpin bowlers in the present study experienced a similar number of positive and negative emotions independent of the phase or importance of the competition. Our finding supports the idea that positive and negative emotions are independent yet can co-exist in the sport context .…”
Section: Emotionsmentioning
confidence: 56%
See 2 more Smart Citations
“…For STRESS, COPING, AND EMOTIONS IN SOCCER 5 example, in a diary-based study of professional rugby union players (Nicholls, Jones, Polman, & Borkoles, 2009), many of the stressors reported for match days were related to other people (opponents, referee, or crowd). With respect to match day coping strategies, blocking (an avoidance strategy) was most frequently cited.…”
mentioning
confidence: 99%